A Single Session of Slackline Training Induces Rapid, Task‐Specific Balance Improvements and Elevated Resting‐State Beta Band Power. - Kenville, Rouven; Groß, Dennis; Helbich, Maximilian; Behrens, Hendrik; Ragert, Patrick; Maudrich, Tom (European Journal of Sport Science, 2026)
Balance training underpins both sports performance and rehabilitation, while its efficacy depends on the amount of training and task difficulty. Here, we characterized neurophysiological changes accompanying the earliest phase of slackline‐specific balance acquisition within a closely matched active‐control design. For this purpose, 35 healthy, slackline‐naïve adults were randomized to a slackline intervention or a time‐matched active control. Before and after training, participants completed slackline single‐leg stance with eyes open (SL‐EO) and eyes closed (SL‐EC), resting‐state electroencephalography (EEG), and tibial‐nerve somatosensory‐evoked potentials (SEP). EEG band‐specific power was quantified after aperiodic correction and resulting change scores were analyzed with non‐parametric mixed models. The intervention group showed larger gains in SL‐EO than control, whereas SL‐EC showed no between‐group difference. Resting‐state EEG exhibited a band‐specific pattern with a greater post‐training increase in beta power in the intervention group, whereas alpha and theta showed no selective group effects. SEP amplitudes did not change pre‐post in either group. Finally, within the intervention group, beta power change did not correlate with individual performance gains. Overall, the present study revealed that resting‐state beta power was sensitive to the earliest phase of slackline‐specific balance acquisition, whereas tibial‐nerve SEP amplitudes remained unchanged. These findings suggest that resting beta power may capture acute post‐practice sensorimotor network changes after a single session of slackline training. Future work should assess generalizability across tasks and populations, combine task‐based EEG with resting measures to link brain state to on‐task control, and track if SEP changes arise over practice to refine models of balance learning. Highlights: Resting‐state EEG showed a selective post‐training increase in beta‐band power after a single session of slackline training, whereas theta and alpha power showed no comparable intervention‐specific effects.Short‐latency tibial‐nerve somatosensory‐evoked potential amplitudes remained unchanged, suggesting that acute slackline learning may not immediately alter stimulus‐locked somatosensory processing.Changes in resting‐state beta power were not significantly associated with individual balance improvements, indicating that beta power may reflect training‐related sensorimotor network state rather than direct performance gains.